Genes and human elite athletic performance - MacArthur, D. G.; North, K. N. (Human Genetics, 2005)
Physical fitness is a complex phenotype influenced by a myriad of environmental and genetic factors, and variation in human physical performance and athletic ability has long been recognised as having a strong heritable component. Recently, the development of technology for rapid DNA sequencing and genotyping has allowed the identification of some of the individual genetic variations that contribute to athletic performance. This review will examine the evidence that has accumulated over the last three decades for a strong genetic influence on human physical performance, with an emphasis on two sets of physical traits, viz. cardiorespiratory and skeletal muscle function, which are particularly important for performance in a variety of sports. We will then review recent studies that have identified individual genetic variants associated with variation in these traits and the polymorphisms that have been directly associated with elite athlete status. Finally, we explore the scientific implications of our rapidly growing understanding of the genetic basis of variation in performance.